Edukasi Program Pekarangan Pangan Lestari di Kota Palu pada Masa Pandemi Covid-19 - Anna Vipta Resti Mauludyani; Moh Fikri Bangsawan Tadorante; Shofiyah Nibras; Devi Lusiana; Fajriani Wahyu Lestari Lestari; Wahyuni Suci Rohani; Nurul Annisa Noch; Nilam Fitrianingsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Palu City is one of the areas affected by covid-19 pandemic. Among all parties, households are severely affected. Income reduction weakens households’ ability to meet their needs for food. To minimize the impact of covid-19 pandemic, education on Home Gardening was implemented on July-August 2020 in 2 location in Palupi Village, Tatanga Subdistrict, Palu City. Program was implemented semi-online through dissemination of tutorial video and demonstration on plant seeding and planting. Moreover, the program was followed by online education on nutritional benefit of the plants via Zoom application. The program was well-implemented with active involvement of the community. Home gardening is potential as alternative to secure household food availability as well as to lessen high household food expenditure due to covid-19 pandemic. Keywords: covid-19, vegetables, demonstration, verticulture, plant seeding